Enhancing Students’ Self-Confidence and Communication Skills through English Public Speaking Training - Hidayah, Siti Nurul; Hasanah, Uswatun (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
This community service program ( Pengabdian Kepada Masyarakat / PKM) was designed to improve students' self-confidence and communication skills through English public speaking training at Madrasah Aliyah (MA) Darunnajah Trenggalek. This research employed a mixed-methods approach, including surveys, classroom observations, and semi-structured interviews. Quantitative data revealed that the training had a favorable impact on students' self-confidence (77.5%) and communication skills (72.9%), both of which were classified as high to moderately high. The program's impact and sustainability acknowledged the highest score (85.4%), demonstrating robust acceptance and perceived significance among students. Qualitative findings from observations and interviews strengthened these results, representing improved student involvement, lessened speaking anxiety, and a heightened willingness to engage in English public speaking training. Nevertheless, certain technical language aspects, particularly pronunciation, continued to pose challenges, emphasizing the need for constant, systematic training. In summary, the findings demonstrate that English public speaking training is an effective community service intervention for enhancing students' affective and communicative skills, with significant potential for continued implementation in madrasah contexts.